월드컵공원 사면지구 식생현황 및 변화 특성 연구 - 한봉호; Han¸ Bong-ho; 박석철; Park¸ Seok-cheol; 최한별; Choi¸ Han-byeol (한국조경학회지, 2023)
본 연구는 월드컵공원 사면지구의 현존식생과 식물군집구조 조사를 통해 매립지 사면지역의 식생구조 특성 및 변화 경향을 밝혀 쓰레기매립지의 식생복원을 위한 기초자료 제공을 목적으로 수행하였다. 현존식생 변화 분석은 1999년, 2003년, 2005년, 2007년, 2008년, 2012년, 2016년, 2021년 현장조사 결과를 비교하여 주요 식생의 변화양상을 파악하였다. 식물군집구조 조사는 자연발생림 내 1999년에 설정한 고정조사구 총 6개소를 대상으로 현장조사를 실시하였다. 현존식생 변화상을 종합해보면 2010년 태풍 곤파스(Kompasu)의 영향으로 사면지구의 아까시나무는 강풍으로 인해 도복되면서 분포면적과 세력 변화가 발생하였고, 특히 건조하고 불량한 식재기반 위에서 군락을 형성하던 습지성 목본인 버드나무는 세력이 감소하게 되었다. 식물군집구조 변화상을 종합해보면 아까시나무군락은 2010년 이후 목본 종수와 개체수가 감소하다가 다시 증가하는 경향을 나타내 향후 아까시나무림이 유지될 것으로 예측되었다. 가죽나무-아까시나무-참오동나무군락은 종수 및 개체수가 아까시나무군락과 유사한 변화를 보였으며, 교목층의 참오동나무와 가죽나무는 도태된 상태로 아까시나무림으로 변화가 예측되었다. 능수버들군락은 아까시나 무림으로 천이된 상태였으며, 일부 조사구에서만 교목층에 아까시나무와 함께 능수버들이 생육하고 있으나 대부분 능수버들이 쇠퇴된 상태이었다. 이들 식생군락은 월드컵공원 사면지구의 대표식생으로서 지속적인 모니터링을 통해 군락별 생태계 변화를 파악해야 하며, 생태계 복원 차원의 매립지 내 조경수식재지 조성에 있어서 중요한 기초자료로 활용할 수 있다. This research intended to reveal the special characteristics of the vegetation structure and the tendency of change of -landfill slope districts, which are reclaimed land, through an investigationsinto the presently existent vegetation and plant community structure of the World Cup Park landfill slope district. For the analysis of changes in vegetation, this study compared the results of field surveys in 1999, 2003, 2005, 2007, 2008, 2012, 2016, and 2021. For the investigation into the plant community structure, a field investigation was carried out in 2021 with six fixed investigation districts designated in 1999 as subjects. To analyze the change in the plant community structure, the past data on the population, the number of the species, and the species diversity by the layer in 2021 were compared and analyzed in the landfill slope district, which is reclaimed land. The changes of the vegetation distribution and the power had been affected by typhoons (Kompasu). Above the plantation foundation, which had been dry and poor, Salix koreensis, marsh woody plants that had formed the community, decreased greatly. The Robinia pseudoacacia community, after the typhoon in 2010, decreased in the number of species and population. Afterward, it showed a tendency to rebound. Regarding the Ailanthus altissima-Robinia pseudoacacia-Paulownia tomentosa community, the number of the species and the population had shown a change similar to the Robinia pseudoacacia community. The Paulownia tomentosa and the Ailanthus altissima have been culled. The slope was predicted as a Future Robinia pseudoacacia forest. The Salix pseudolasiogyne community has been transitioning to a Robinia pseudoacacia forest. Only some enumeration districts, the Robinia pseudoacacia forests and the Salix pseudolasiogyne, had been growing. However, most had been in been declining. It was predicted that this community will be maintained as a Robinia pseudoacacia forest in the future. As these vegetation communities are the representative vegetation of the landfill slope districts, which is reclaimed land, there is a need to understand the ecosystem changes of the community through continuous monitoring. The results of this research can be utilized as a basic material for the vegetation restoration of reclaimed land.